ENT 530 91Doorgift / Nurul Aziera Ahmad Rafia'i - Ahmad Rafia'i, Nurul Aziera (2018)
91 doorgift is my commercial business name. Through this business, I am selling door gifts for any occasion. Although most of my customer ordered for wedding door gift, there are plenty of them that ordered for different event such as birthdays, family day and gathering. I decided to open up this door gifts business because I saw the opportunity in it while I was attending a wedding of a relative. When I looked at the door gift I received I thought to myself that it does not seem that hard to make such gift. Thus, I searched for suppliers that could offer me the stocks in lower prices and luckily I already had the designing skill that has helped me a lot in designing customer's demands. After that, I started making social media accounts to promote my new product. My initial business plan is to make it convenient for the people who want to throw an event but is in rush and had little planning as my business accepts late small orders and can deliver within 2 working days. However, fortunately, my business has grew bigger and a lot of customers have ordered bigger amount of order and with that I could not really accept a lot of orders as the products are only prepared by the_ help of siblings.